Immunities and Criminal Proceedings: Vol II (Equatorial Guinea v. France) - International Court of Justice (United Nations, 2022)
This case was entered on the Court’s General List on 13 June 2016 under number 163 and was the subject of a Judgment delivered on 11 December 2020. The documents relating to the case include the Application instituting proceedings, the Request for the indication of provisional measures and the written proceedings (Volume I) as well as the verbatim records of public hearings (Volume II).